Genomic Evolution of Staphylococcus aureus During Artificial and Natural Colonization of the Human Nose - Goyal, Manisha; Javerliat, Fabien; Palmieri, Mattia; Mirande, Caroline; van Wamel, Willem; Tavakol, Mehri; Verkaik, Nelianne J.; van Belkum, Alex (Frontiers in Microbiology, 2019)
Staphylococcus aureus can colonize the human vestibulum nasi for many years. It is unknown whether and, how S. aureus adapts to this ecological niche during colonization. We determined the short (1 and 3 months) and mid-term (36 months) genomic evolution of S. aureus in natural carriers and artificially colonized volunteers. Eighty-five S. aureus strains were collected from 6 natural carriers during 3 years and 6 artificially colonized volunteers during 1 month. Multi-locus sequence typing (MLST) and single nucleotide polymorphism (SNP) analysis based on whole-genome sequencing (WGS) were carried out. Mutation frequencies within resident bacterial populations over time were quantified using core genome SNP counts (comparing groups of genomes) and pairwise SNP divergence assessment (comparing two genomes from strains originating from one host and sharing identical MLST). SNP counts (within 1–3 months) in all naturally colonizing strains varied from 0 to 757 (median 4). These strains showed random and independent patterns of pairwise SNP divergence (0 to 44 SNPs, median 7). When the different core genome SNP counts over a period of 3 years were considered, the median SNP count was 4 (range 0–26). Host-specific pairwise SNP divergence for the same period ranged from 9 to 57 SNPs (median 20). During short term artificial colonization the mutation frequency was even lower (0–7 SNPs, median 2) and the pairwise SNP distances were 0 to 5 SNPs (median 2). Quantifying mutation frequencies is important for the longitudinal follow-up of epidemics of infections and outbreak management. Random pattern of pairwise SNP divergence between the strains isolated from single carriers suggested that the WGS of multiple colonies is necessary in this context. Over periods up to 3 years, maximum median core genome SNP counts and SNP divergence for the strains studied were 4 and 20 SNPs or lower. During artificial colonization, where median core genome SNP and pairwise SNP distance scores were 2, there is no early stage selection of different genotypes. Therefore, we suggest an epidemiological cut off value of 20 SNPs as a marker of S. aureus strain identity during studies on nasal colonization and also outbreaks of infection.